Anti-Inflammatory Effects of Intra-Articular Hyaluronic Acid: A Systematic Review. (January 2019) - Altman, Roy; Bedi, Asheesh; Manjoo, Ajay; Niazi, Faizan; Shaw, Peter; Mease, Philip
Objective: Osteoarthritis (OA) is one of the leading causes of disability in the adult population. Common nonoperative treatment options include nonsteroidal anti-inflammatory drugs (NSAIDs), intra-articular corticosteroids, and intra-articular injections of hyaluronic acid (HA). HA is found intrinsically within the knee joint providing viscoelastic properties to the synovial fluid. HA therapy provides anti-inflammatory relief through a number of different pathways, including the suppression of pro-inflammatory cytokines and chemokines. Methods: We conducted a systematic review to summarize the published literature on the anti-inflammatory properties of hyaluronic acid in osteoarthritis. Included articles were categorized based on the primary anti-inflammatory responses described within them, by the immediate cell surface receptor protein assessed within the article, or based on the primary theme of the article. Key findings aimed to describe the macromolecules and inflammatory-mediated responses associated with the cell transmembrane receptors. Results: Forty-eight articles were included in this systematic review that focused on the general anti-inflammatory effects of HA in knee OA, mediated through receptor-binding relationships with cluster determinant 44 (CD44), toll-like receptor 2 (TLR-2) and 4 (TLR-4), intercellular adhesion molecule-1 (ICAM-1), and layilin (LAYN) cell surface receptors. Higher molecular weight HA (HMWHA) promotes anti-inflammatory responses, whereas short HA oligosaccharides produce inflammatory reactions. Conclusions: Intra-articular HA is a viable therapeutic option in treating knee OA and suppressing inflammatory responses. HMWHA is effective in suppressing the key macromolecules that elicit the inflammatory response by short HA oligosaccharides.